2017
DOI: 10.21273/hortsci12192-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus Rates on Growth, Yield, and Postharvest Quality of Tomato in a Calcareous Soil

Abstract: Phosphorous (P) has a significant role in root growth, fruit and seed development, and plant disease resistance. Currently, no P fertilizer recommendations are available for vegetables grown on calcareous soils in Florida. The objective of this study was to evaluate the impact of different P rates on leaf tissue P concentration (LTPC), plant growth, biomass accumulation, fruit yield, and postharvest quality of tomato (Solanum lycopersicum L.) grown on a calcareous soil. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Furthermore, P is known to contribute more in yield components like flower, seed formation, and ripening rather than vegetative growth (Rehman and Qayyum 2020). In some other situations, researchers have also reported non-significant effect of P on plant height (Ali et al 2014;Zhu et al 2017). We found increase in spike length, number of grain per spike, and 1000-grain weight which are in lined with Rehman and Qayyum (2020), who reported that phosphorus plays prominent roles in plant physiological processes, but its role is crucial in cell division, formation of seeds, crops maturation, and flower formation.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, P is known to contribute more in yield components like flower, seed formation, and ripening rather than vegetative growth (Rehman and Qayyum 2020). In some other situations, researchers have also reported non-significant effect of P on plant height (Ali et al 2014;Zhu et al 2017). We found increase in spike length, number of grain per spike, and 1000-grain weight which are in lined with Rehman and Qayyum (2020), who reported that phosphorus plays prominent roles in plant physiological processes, but its role is crucial in cell division, formation of seeds, crops maturation, and flower formation.…”
Section: Discussionsupporting
confidence: 86%
“…The taste and flavor of tomatoes and their antioxidant content differ according to growing conditions, cultivation techniques, cultivars, and cultivation time [10][11][12][13]. Soil P is a well-known key nutrient for tomato production and other crops, such as maize [14] and soybean [15], and maintaining adequate levels of P in the soil is important for maximizing tomato growth and development [16][17][18]. However, the effect of different P fertilizer amounts on the growth performance of tomato plants remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…y P value of the analysis of variance. medium-size fruit, were mainly from the first and second harvests (Zhu et al, 2017a). As a result, the significantly affected tomato marketable yields from FH in 2014 and FSH in 2015 were selected to regress against STP.…”
Section: Discussionmentioning
confidence: 99%